2019
DOI: 10.1128/mra.01032-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Stenotrophomonas maltophilia Podophage Ponderosa

Abstract: Stenotrophomonas maltophilia is a Gram-negative bacterium that is emerging as a multidrug-resistant global opportunistic pathogen. Here, we describe the genome of the T7-like S. maltophilia podophage Ponderosa, with 54 predicted protein-coding genes and a 493-bp terminal repeat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…It is possible that the competitive advantage of type IV pili to aid in the colonization of plants [ 2 , 31 ] has selected for the use of these structures as phage receptors in soil microbes. It is unknown if the type IV pilus is a favoured receptor of S. maltophilia phages isolated from other environmental sources, such as water and sewage, as the receptors for these phages have not been examined [ 12 , 13 , 14 , 15 , 16 , 22 , 23 , 24 , 32 ]. However, the T4-like virulent phage Smp14 has been observed to bind to the poles of S. maltophilia cells by TEM [ 21 ] where type IV pili are normally expressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the competitive advantage of type IV pili to aid in the colonization of plants [ 2 , 31 ] has selected for the use of these structures as phage receptors in soil microbes. It is unknown if the type IV pilus is a favoured receptor of S. maltophilia phages isolated from other environmental sources, such as water and sewage, as the receptors for these phages have not been examined [ 12 , 13 , 14 , 15 , 16 , 22 , 23 , 24 , 32 ]. However, the T4-like virulent phage Smp14 has been observed to bind to the poles of S. maltophilia cells by TEM [ 21 ] where type IV pili are normally expressed.…”
Section: Resultsmentioning
confidence: 99%
“…The use of phages for human therapy requires extensive phage characterization, including host range analysis, genomic characterization and identification of potential moron genes, lifestyle determination and identification of cell surface receptors. In the last two decades, numerous phages against S. maltophilia have been isolated and characterized to various extents for their therapeutic potential [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Herein we describe the isolation and characterization of a novel S. maltophilia phage, AXL3, unrelated to any phages currently sequenced in the NCBI database.…”
Section: Introductionmentioning
confidence: 99%
“…No holin gene could be reliably identified, and only one tail fiber was identified with confidence. Genome comparison analysis revealed that Ptah is most closely related to S. maltophilia phage Ponderosa (GenBank accession number MK903280 ) ( 22 ), with 51 shared proteins (BLASTp; E value, <0.001) and 83.25% genome-wide nucleotide identity, as determined by progressiveMauve. Like phage Ponderosa, phage Ptah is T7-like in genome organization and size.…”
Section: Announcementmentioning
confidence: 99%
“…The genome termini were analyzed using PhageTerm ( 21 ), but the results were not conclusive. Phage Pepon shared the highest similarity with the S. maltophilia T7-like podophage Ponderosa (GenBank accession number MK903280 ) ( 22 ), with 90.6% genome-wide nucleotide identity, as determined using ProgressiveMauve, and 52 similar proteins (BLASTp; E value, <0.001). The predicted lysis cassette of Pepon appears to be bisected by the small and large terminases, with a class II holin upstream of the terminases and a downstream signal-arrest-release (SAR) endolysin and partially overlapping i-spanin/o-spanin.…”
Section: Announcementmentioning
confidence: 99%